Cytochrome c oxidase‐modulatory near‐infrared light penetration into the human brain: Implications for the noninvasive treatment of ischemia/reperfusion injury. Issue 3 (9th November 2020) - Morse, Paul T.; Goebel, Dennis J.; Wan, Junmei; Tuck, Samuel; Hakim, Lara; Hüttemann, Charlotte L.; Malek, Moh H.; Lee, Icksoo; Sanderson, Thomas H.; Hüttemann, Maik
Abstract: Near‐infrared light (IRL) has been evaluated as a therapeutic for a variety of pathological conditions, including ischemia/reperfusion injury of the brain, which can be caused by an ischemic stroke or cardiac arrest. Strategies have focused on modulating the activity of mitochondrial electron transport chain (ETC) enzyme cytochrome c oxidase (COX), which has copper centers that broadly absorb IRL between 700 and 1, 000 nm. We have recently identified specific COX‐inhibitory IRL wavelengths that are profoundly neuroprotective in rodent models of brain ischemia/reperfusion through the following mechanism: COX inhibition by IRL limits mitochondrial membrane potential hyperpolarization during reperfusion, which otherwise causes reactive oxygen species (ROS) production and cell death. Prior to clinical application of IRL on humans, IRL penetration must be tested, which may be wavelength dependent. In the present study, four fresh (unfixed) cadavers and isolated cadaver tissues were used to examine the transmission of infrared light through human biological tissues. We conclude that the transmission of 750 and 940 nm IRL through 4 cm of cadaver head supports the viability of IRL to treat human brain ischemia/reperfusion injury and is similar for skin with different skin pigmentation. We discuss experimental difficulties of working with fresh cadavers and strategies to overcome them as a guide for future studies.